The first Chief Justice : John Jay and the struggle of a new nation - Dillon, Mark C. (SUNY series in American constitutionalism., 2022)
"Chronicles the efforts of the first Chief Justice of the US Supreme Court to establish a federal court system during the country's uncertain early years"--